Análise da implantação dos Trabalhos Colaborativos de Autoria em escolas da região de Itaquera, no município de São Paulo - Costa, Valter de Almeida (2018)
This study examined, in the curricular reorganization process promoted by the Municipal Secretary of Education of São Paulo, which instituted the Authorial Cycle as the final stage of Primary Education, the aspects related to the Collaborative Study of Authorship, the C.S.A., which was developed by students of this cycle, under the guidance of their teachers. The general objective was to analyze the process of implanting these Collaborative Studies of Authorship by identifying their difficulties and achievements in the schools observed. The specific objectives of the study constitute an analysis of how this project, in these schools, addressed or not more political themes, from the perspective of social criticism, in the context of an era in which there is increasing pressure for the progressive depoliticization of the curriculum